Efektivitas Proses Pemuatan Semen Curah terhadap Kinerja Operasional Kapal yang Diageni oleh PT. Pelayaran Multi Jaya Samudera Belawan - Sakti Las Martua Sihite; Suratni Ginting; Lilis Lilis (Port Management and Maritime Administration Journal, 2026)
This study aims to analyze the effectiveness of bulk cement loading processes on the operational performance of vessels agented by PT. Pelayaran Multi Jaya Samudera Belawan. Bulk cement loading is a complex logistical activity at specialized port terminals that requires intensive coordination between the vessel, agency, and terminal to comply with international safety standards such as the IMSBC Code. The research method used was descriptive qualitative, with data collection techniques including direct field observations, interviews with the company's operational staff, and documentation studies conducted during the internship period. The research findings indicate that loading effectiveness is significantly influenced by the readiness of cargo handling equipment, such as pneumatic or conveyor systems, as well as the timeliness of agency administration in processing ship documents. Although the process generally runs well, obstacles were identified in the form of technical malfunctions of loading equipment and weather factors that frequently hinder operational speed. The conclusion of this research emphasizes that enhancing technical supervision and strengthening communication between the agent and port terminal authorities are crucial to minimizing vessel dwelling time, thereby optimizing operational performance and cost efficiency for ship owners.